Evaluation of sorbic acid and sulfur dioxide as preservatives for ladu orange juice - Cipriano, Ofelia A.
Sample of ladu orange juice heated at 185 °F were stored at room temperature (82 ± 2 °F) for 25 days without preservatives and with sorbic acid at the 500 and 1000 ppm levels, and sulfur dioxide at the 350 and 600 ppm levels. All the juice samples were subjected to microbiological, physicochemical (pH, %TA, %SS) and organoleptic tests during their storage. In general, addition of preservatives resulted in lower microbial growth, less changes in pH and total acids, and lower soluble solids utilization as compared with the control. The microbial counts of the treated samples reached the zero count o the 4th day of storage, except replicates of 1 of the 1000 ppm sorbic acid and 350 ppm of SO2 treated samples. The treated samples, except the 350 ppm SO2 samples, had no counts till the end of storage, while the controls had growth during the entire storage period. The 350 ppm SO2 treated samples had no counts on the 11th day of storage but counts of 10 yeasts per ml of juice were again obtained on the 17th and 24th day of replicates 2 and 1, respectively. The surviving microorganisms were mostly yeast and few molds. The changes in pH and total acids were only slight, but the controls showed the greatest changes in values. The controls also had the greatest percentage of soluble solids utilized, an average of 43%, while the treated samples had only 7-13% soluble solids utilized. The treated samples were usually rated better in order and flavor than the controls. The color of the SO2 treated samples were better than the controls and the sorbic acid treated samples. Bitterness, peely and astringent taste were evident in the juice even before the addition of the preservatives.